Resilience-Focused HIV Care to Promote Psychological Well-Being During COVID-19 and Other Catastrophes - Brown, L. Lauren; Martin, Erika G.; Knudsen, Hannah K.; Gotham, Heather J.; Garner, Bryan R. (Frontiers in Public Health, 2021)
The COVID-19 pandemic has adversely affected people with HIV due to disruptions in prevention and care services, economic impacts, and social isolation. These stressors have contributed to worse physical health, HIV treatment outcomes, and psychological wellness. Psychological sequelae associated with COVID-19 threaten the overall well-being of people with HIV and efforts to end the HIV epidemic. Resilience is a known mediator of health disparities and can improve psychological wellness and behavioral health outcomes along the HIV Continuum of Care. Though resilience is often organically developed in individuals as a result of overcoming adversity, it may be fostered through multi-level internal and external resourcing (at psychological, interpersonal, spiritual, and community/neighborhood levels). In this Perspective, resilience-focused HIV care is defined as a model of care in which providers promote optimum health for people with HIV by facilitating multi-level resourcing to buffer the effects of adversity and foster well-being. Adoption of resilience-focused HIV care may help providers better promote well-being among people living with HIV during this time of increased psychological stress and help prepare systems of care for future catastrophes. Informed by the literature, we constructed a set of core principles and considerations for successful adoption and sustainability of resilience-focused HIV care. Our definition of resilience-focused HIV care marks a novel contribution to the knowledge base and responds to the call for a multidimensional definition of resilience as part of HIV research.